Protocol for a hybrid type I randomized controlled trial evaluating the effectiveness and implementation of a nurse home visiting program for adolescent pregnancy on maternal and infant outcomes - Becker, Natália; Soares, Vinícius Nagy; Chou, Débora Tseng; Neto, Emilio Abelama; da Silva, Letícia Aparecida; Osório, Ana Alexandra Caldas; Nascimento, Ariana Gomes; Marchisio, Vinnie; Menegócio, Alexandro Marcos; Pereira, Adriana Tebaldi; Haas, Andrea Bernardinetti Muller; Pina-Oliveira, Alfredo Almeida; et al. (Frontiers in Psychiatry, 2025)
BackgroundAdolescent pregnancy poses significant public health challenges, particularly among vulnerable populations. Nurse home visiting programs, such as Primeiros Laços, show promise in improving maternal and child health outcomes, yet their integration into primary healthcare remains underexplored, especially in low-resource settings.Aimto evaluate the effectiveness and feasibility of integrating Primeiros Laços into primary healthcare services across two municipalities of the state of São Paulo, Brazil.MethodA hybrid type I randomized controlled trial will be conducted to assess both the clinical effectiveness and implementation feasibility of the program. The study will enroll 200 pregnant adolescents (aged 14–24), who will be randomized into two groups: an intervention group, receiving up to 38 structured nurse home visits from pregnancy until the child’s 24th month, and a control group, receiving standard care. The home visits will focus on promoting maternal and child health, positive parenting practices, and secure mother-infant attachment. Data collection will include validated tools to assess maternal mental health (Alcohol, Smoking, and Substance Involvement Screening Test - ASSIST, Edinburgh Postnatal Depression Scale – EPDS, Tilburg Pregnancy Distress Scale – TPDS, and Generalized Anxiety Disorder-7 - GAD-7), infant development (Infant Behavior Questionnaire – Revised - IBQ-R, Bayley Scales of Infant and Toddler Development - Bayley-III, and Ages and Stages Questionnaire - ASQ-3), mother-infant interactions (Ainsworth’s Maternal Sensitivity Scales, and Maternal Postnatal Attachment Scale), and the quality of the home environment (Infant/Toddler Home Observation for Measurement of the Environment - IT-HOME). Implementation outcomes will be evaluated using the EPIS (Exploration, Preparation, Implementation, Sustainment) framework, semi-structured interviews with key stakeholders (e.g., healthcare providers, program staff, and participants), and the Program Sustainability Assessment Tool to identify factors influencing long-term program viability. Quantitative data will be analyzed using an intention-to-treat approach, while qualitative data will undergo thematic analysis to identify barriers and facilitators to program integration.Expected resultsThe intervention is hypothesized to improve maternal and infant outcomes, such as prenatal care adherence, breastfeeding rates, and cognitive and emotional development, while fostering positive parenting practices and secure mother-infant attachment. The implementation analysis will identify key barriers and facilitators to program integration.ImpactThis study will provide evidence on the clinical and practical benefits of nurse home visiting programs for adolescent pregnancy in primary care, guiding their integration, scale-up, and potential adaptation for global maternal and child health initiatives. The findings aim to inform policymakers and healthcare providers on effective strategies to address adolescent pregnancy and improve health outcomes in low-resource settings.